Tierra, territorio y autonomía: la lucha política del movimiento social mapuche en la sociedad neoliberal chilena - Gómez Leitón, Juan Carlos (2016)
From the end of the 20th Century, the indigenous people of the America have become a "new political actor"; in the case of the Mapuche in Chile these have taken up a struggle in defense of their territories, cultural identity and their own survival threatened by neoliberal policies that since from the time of the Pinochet dictatorship have introduced reforms like private property instead of cornmunal holdings which have significantly altered their economic, social and cultural structures. Via new organizations, articuJated through a territorial base, distanced from national organizations, the Mapuche defend themselves as independent of the state and institutions of Chilean society. However, their demands for land are not clear and their other demands like autonomy are violently countered by the state, which has strengthened the neoliberal order.